Three resveratrolâs oligomers from the stem bark of H. gregaria (dipterocarpaceae) and their toxicity and citotoxicity - ., Sahidin; Hakim, Euis H.; Syah, Yana M.; Juliawaty, Lia D.; Achmad, Sjamsul A.; Latip, Jalifah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Three resveratrol oligomers have been isolated from the stem bark of H. gregaria including a resveratrol trimer i.e. Î±-viniferin (1), and two resveratrol tetramers i.e. vaticanol B (2) and hopeaphenol (3). These structures were determined by spectroscopic evidence including UV, IR, 1H , 13C NMR and compared with that of the reported data in the literatures. Activities of the compounds were determined toward brine shrimp Artemia salina (toxicity) and murine leukemia P-388 cells (cytotoxicity). The compound 1 is the most active against A. salina (LC50 = 49,0 Â± 5,8 Î¼g/mL), and the compound 3 has very active level toward murine leukemia P-388 cells (LC50 = 5,7 Â± 0,3 Î¼M).Key words : Resveratrol oligomers, H. gregaria, toxicity, and cytotoxicity.